Income levels, governance and inclusive human development in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study examines how income-driven governance affects inclusive human development in Sub-Saharan Africa with data for the period 2000-2012. The empirical evidence is based on the Generalised Method of Moments (GMM) and Tobit regressions. Nine bundled and unbundled concepts of governance are used: political (voice & accountability and political stability/no violence), economic (government effectiveness and regulation quality) and institutional (corruption-control and the rule of law) governances. The main finding is that "middle income"-driven governance has a higher effect on inclusive human development than "low income"-driven governance. Policy implications are discussed in the light of: (i) the contemporary relevance of findings; (ii) the pivotal role of a higher income level in the post-2015 sustainable development agenda; and (iii) inconsistent strands in the literature and in foreign aid policies.
Keywords: D31; I10; I32; K40; O55; 330; Inclusive development; Income levels; Governance; Africa